Cystotomy with or without fibrinogen clot removal for refractory cystoid macular edema secondary to branch retinal vein occlusion - Hiroko Yamada (Nature Portfolio, 2021)
Abstract To demonstrate the long-term effect of cystotomy with or without fibrinogen clot removal for treatment-resistant cystoid macular edema (CME) secondary to branch retinal vein occlusion (BRVO). Retrospective clinical study. We retrospectively analyzed medical records of 22 eyes of 22 patients with treatment-resistant CME secondary to BRVO with 12 months observation after cystotomy with or without fibrinogen clot removal. Patients included 11 women and 11 men. The mean ± SD age was 72.7 ± 10.2 years. LogMAR-converted best corrected visual acuity (BCVA) was statistically better at 12 months after surgery (0.30 ± 0.30) than preoperative BCVA (0.39 ± 0.27) (p = 0.01). The central sensitivity of microperimetry (dB) was maintained during follow-up (preoperative sensitivity: 25.4 ± 4.1, postoperative sensitivity at 12 months after the surgery: 25.9 ± 4.2, p = 0.69). Twelve months after surgery, there was a significant improvement in the central retinal thickness (CRT) on optical coherence tomography (OCT) (303.7 ± 80.1) (μm) compared with the preoperative CRT (524.2 ± 114.8) (p < 0.01). In 12 months, CME recurred in 3 of 22 eyes. The preoperative reflectivity in cystoid cavity on OCT was significantly higher in patients with fibrinogen clot removal (n = 5) than in patients without fibrinogen clot removal (n = 17) (p < 0.01). For treatment-resistant CME secondary to BRVO, Cystotomy with or without fibrinogen clot removal may be one of the treatment options.